Rare Earth Metal Ion-Associates in Ln3+—CO32−—H2O System - Tatiana Litvinova; Stepan Gerasev; Vasiliy Sergeev; Egor Lidanovskiy (Metals)
This study focused on the nature of rare earth metal complex compounds that can form during the carbonate–alkaline processing of industrial waste materials, such as phosphogypsum and red mud, at 70–100 °C and 1–10 atm. Experimental findings revealed that the dissolution of synthetic carbonates of rare earth elements (REEs) in a concentrated carbonate-ion medium (3 mol/L) leads to the formation of ion-associates of varying strengths. Light (lanthanum, praseodymium, and neodymium) and medium (samarium) REE groups exhibited a tendency to form loose ion-associates, whereas heavy REEs (terbium, dysprosium, holmium, erbium, thulium, lutetium, and yttrium) formed close ion-associates. To confirm the existence of these ion-associates, the specific conductivity of solutions was measured after dissolving thulium (III) and samarium (III) carbonates at phase ratios ranging from 1:2000 g/mL to 1:40 g/mL in a potassium carbonate medium. The decay of ion-associates, leading to the precipitation of rare earth metal (III) carbonates, was tested in an ammonium carbonate medium. Thermal decomposition of ammonium carbonate at 70–75 °C during 1–4 h was accompanied by full rare earth carbonates’ sedimentation and its in-the-way separation into groups because of the varied strength of ion-associates. The results of this study provide a basis for developing processes to separate rare earth metals into groups during their carbonate–alkaline extraction into solution.